Software: Protection, Licensing and Rewarding Researchers in Computer Science – An Overview of Challenges in the European Innovation Ecosystem (Informatica, 2022)
With the transition of innovation to the digital sphere, the software has become an essential part of contemporary inventions and creations. It is also an essential part of intellectual property. The state of software protection in the European innovation ecosystem can still not be considered fully regulated. However, researchers in computer science also face several challenges when exploiting intellectual property rights in software. The field, therefore, offers opportunities for researching, which should steer research to (1) present the critical points and (2) update some of the legal frameworks to address more clearly the field that deals with the issue of remuneration for researchers in computer science. The overview paper discusses software, focusing mainly on the challenges that researchers in computer science face in protecting and licensing software in the European innovation ecosystem. The following paper presents the state of the researcher’s remuneration under protection and licensing.